Development Strategy of Kemiri Tourism Village in Jember Regency - Prakosa, Redo Mandra (Jurnal Mengkaji Indonesia, 2024)
Abstract: Kemiri village is a village in the western part of Jember district exactly on the slopes of Mount Argopuro that is well-known with The Tancak Waterfall. Kemiri Village is very strategic with fresh air condition that makes Kemiri Village become one of the tourist destinations in East Java, especially in Jember Regency. Purpose: The research aims to identify the potential and the existing conditions in Kemiri Tourism Village, identify internal and external factors in the development of Kemiri Village Tourism, and formulate the main or grand strategies and alternative strategies as well as programs that be able to implement on the process of development Kemiri Village Tourism. Design/Methodology/Approach: The data collection techniques use observations, interviews, documentation, focus group discussions, library studies, and questionnaires. Also, the data analysis techniques use qualitative descriptive, IFAS, EFAS, IE and SWOT Matrix Analysis Findings: Based on the results of IFAS Matrix Analysis, the internal factors that became the main strength of the Kemiri Village Tourism is about ‘Kemiri Village Tourism social capital and participation of the community’ with a score 0,364. Also, the main weakness of the Kemiri Village Tourism about ‘unscheduled services in tourism activities’ with a score 0,032. On the result of EFAS Matrix Anlysis, it shows that the main opportunity of the Kemiri Village Tourism is ‘open the employment opportunities around tourist attractions’ with a score 0,300. Also, the main threat of the Kemiri Village Tourism is ‘decrease the value and local wisdom’ and ‘conversion of agricultural land for tourism needs’ with each score 0,029. The main strategy based on the IE Matrix analysis that can be implemented by the Kemiri Village Tourism are hold and maintain means the market penetration and the product development. The alternative strategies from the results of SWOT Matrix Analysis obtained as many as 13 strategies with programs formulated on each of these strategies.